CHEMICAL AND NUTRITIONAL STUDY VARIETY OF THE ROOT OF Polymnia sonchifolia "YACON" - Chasquibol S., Nancy (2002)
The yacon root is a member of the sunflower family. The roots of yacon has inuline. lnuline is a polyfructosane, which helps to moderate blood sugar levels (pass through the digestive tract unmetabolized). Yacon therefore has considerable value to dieters and people with diabetes. The quantitative analysis shows mineral macronutrients (Na, K, Mg, Ca, P). and micronutrients (Fe, Zn, Mn). The qualitative analysis shows very important secondary metabolites (amino acids, carbohydrate, reducing sugars, flavonoides)